Asuhan Keperawatan pada Ibu Post Sectio Caesarea Di Ruangan Kebidanan RSUD Poso: Nursing Care For Mothers Post Sectio Caesarea In The Obstetrics Room Of Hospital Poso - Siti Nurazizah; Nirva Rantesigi (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Introduction: post sectio caesarean delivery has a five times greater risk of complications compared to normal delivery, problems that commonly occur in post section caesarean mothers are postpartum bleeding, infection, and swollen breasts. For this reason, comprehensive nursing care is needed and improving health in clients can be done by a nursing care approach. The purpose of this study was to provide nursing care for post sectio caesarea mothers in the obstetrics room at Poso Hospital. Methods : The research method is using a descriptive method with a case study approach of 1 patient of post sectio caesarea mother. Results: assessment of the patient complained of pain in the abdomen after cesarean section surgery, the pain was felt like stabbing, the pain disappeared, the patient looked grimacing, there was a surgical wound, there were 14 stitches, wound size 11 cm, wound width 0.2 cm, pain scale 8, blood pressure 110/80 mmhg, breathing 20x / m, pulse 80x / m, temperature 37 ̊C post section caesarea 6 hours. The patient said the milk had not come out, the patient said the baby cried when breastfed, the milk did not gush or drip, the nipples looked flat, the baby did not want to suck. Nursing problems acute pain, ineffective breastfeeding. Nursing Interventions Pain management, relaxation therapy, positioning, mobilization support, analgesic breastfeeding education, and giving the baby the opportunity to breastfeed. Implementation was carried out for 5 evaluation results showed reduced pain, the patient said he could do activities, the patient no longer complained of pain in the abdomen, pain scale 3, the patient said the milk had started to come out, the patient said the baby had not cried when breastfed, the milk had come out, the patient looked more relaxed and comfortable. Conclusion: pain management, relaxation therapy, positioning, mobilization support, giving analgesic breastfeeding education, and providing opportunities for babies to breastfeed are effective in providing nursing care to post section caesarea mothers. Suggestions patients can carry out nursing interventions independently according to what is taught by researchers.